2011
DOI: 10.1208/s12249-011-9675-1
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine Tartrate–Eudragit Long-Acting Nanoparticles: Formulation, Optimization, In Vitro and In Vivo Evaluation

Abstract: Abstract. In the present study, an effort was made to design prolonged release Eudragit nanoparticles of brimonidine tartrate by double emulsion-solvent evaporation technique for the treatment of open-angle glaucoma. The effect of various formulation variables like initial drug amount, lecithin proportion, phase volume and pH, secondary emulsifier and polymer proportion were studied. Various process variables like energy and duration of emulsification, lyophilization on the characteristics of nanoparticles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 34 publications
1
35
0
2
Order By: Relevance
“…For both groups, normal saline was administered in the same location of the right eye. Results showed that the nanoparticles were well tolerated, with no signs of irritation or toxicity 17. Moreover, the BRT nanoparticles decreased the elevated IOP in rabbits with glaucoma for a longer period of time compared to the conventional drop formulation (p<0.0001) 17…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For both groups, normal saline was administered in the same location of the right eye. Results showed that the nanoparticles were well tolerated, with no signs of irritation or toxicity 17. Moreover, the BRT nanoparticles decreased the elevated IOP in rabbits with glaucoma for a longer period of time compared to the conventional drop formulation (p<0.0001) 17…”
Section: Resultsmentioning
confidence: 94%
“…Bhagav and colleagues used brimonidine tartrate (BRT) encapsulated Eudragit nanoparticles to study prolonged release of BRT 17. The Eudragit nanoparticles are inert polymeric resin copolymers used to entrap lipophilic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Dialysis sacs are also used in combination with official USP dissolution/release apparatus (such as USP apparatus 1 and 2). For example, a dialysis sac method was used in the USP apparatus 1 (basket type) to study brimonidine tartrate release from Eudragit long acting nanoparticles (26). This study demonstrated that brimonidine tartrate release from the nanoparticles was controlled by non-Fickian anomalous transport, which was very valuable to assist in formulation optimization to achieve the desired drug release behavior (26).…”
Section: Current In Vitro Dissolution/release Testing Methodsmentioning
confidence: 99%
“…For example, a dialysis sac method was used in the USP apparatus 1 (basket type) to study brimonidine tartrate release from Eudragit long acting nanoparticles (26). This study demonstrated that brimonidine tartrate release from the nanoparticles was controlled by non-Fickian anomalous transport, which was very valuable to assist in formulation optimization to achieve the desired drug release behavior (26). However, due to the hindrance to drug diffusion through the dialysis membranes as well as the lack of adequate agitation inside the dialysis sacs themselves, violation of sink conditions has been reported (13, 19, 27, 28).…”
Section: Current In Vitro Dissolution/release Testing Methodsmentioning
confidence: 99%
“…The latter is cationic copolymer synthesized from acrylic acid and methacrylic acid esters with 5% quaternary ammonium groups (16). Like Eudragit® RL100, Eudragit® RS100 is able to develop stable non-irritant nano-dispersions suitable for ocular drug delivery (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%